TEKSTUR DALAM ESTETIKA KERAMIK - Noor Sudiyati (Institut Seni Indonesia Yogyakarta, 2021)
Human’s daily feeling such as: happy, disappoint, jealous, sorrow, expecting, calm, quiet, etc. Are the human’s feelings that artenately exist in daily activity and sometimes in memory. Sometimes, feelings could be revealed when spurred on stimulatedthings, especially hand made craft (art). Which comprise the expressition of the creator / artist. Artifac or ceramic have aesthetic value that could stimulate people/ audiences feeling. The Texture of a ceramic, the real texture, the rough texture, or the pseudo texture has allure to re-evoke human’s feelings that ever experienced.Rasa dimiliki oleh manusia sehari-hari seperti : bahagia, senang, kecewa, cemburu, sedih, pilu, berharap, tenang, hening, dan lain sebagainya adalah perasaan manusia yang ada silih berganti dalam keseharian, terkadang terendapkan dalam memori. Rasa adakalanya bisa terungkap lagi ketika terpacu oleh rangsangan benda-benda, terutama benda-benda buatan tangan (seni ) yang mengandung ekspresi dari perupanya/ senimannya. Artefak atau benda keramik memiliki estetika yang mampu merangsang perasaan orang /audiens . Tekstur pada keramik, baik itu tekstur nyata, kasar, ataupun tekstur semu memiliki daya pikat untuk membangkitkan lagi perasaan-perasaan manusia yang telah dialaminya.